2008
DOI: 10.1016/j.ecoenv.2007.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Platinum, palladium and rhodium release from vehicle exhaust catalysts and road dust exposed to simulated lung fluids

Abstract: The risk associated with the inhalation of platinum group element (PGE) emissions from vehicle exhaust catalysts (VECs) has been investigated by extracting road dust and milled auto catalyst with simulated lung fluids. Gamble's solution (representative of the interstitial fluid of the deep lung) and artificial lysosomal fluid (ALF) (representative of the more acidic environment within the lung) were employed as extraction fluids. The highest PGE release was observed in ALF, implying that inhaled particles woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(113 citation statements)
references
References 41 publications
4
99
2
1
Order By: Relevance
“…To this solution, 3.2 g of pepsin were added, dissolved well and finally the volume was make up to 1 litre using bi-distilled water. Artificial lysosomal fluid and Gamble solution were prepared according to Colombo et al, 2008. Indium at level of 1 ppm was also added to the prepared leaching agents as an internal standard in order to overcome non-spectral interferences as well as errors related to manual sample handling steps.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…To this solution, 3.2 g of pepsin were added, dissolved well and finally the volume was make up to 1 litre using bi-distilled water. Artificial lysosomal fluid and Gamble solution were prepared according to Colombo et al, 2008. Indium at level of 1 ppm was also added to the prepared leaching agents as an internal standard in order to overcome non-spectral interferences as well as errors related to manual sample handling steps.…”
Section: Reagents and Materialsmentioning
confidence: 99%
“…Citrate was used instead of proteins to avoid foaming and acetate instead of organic acids. Gamble's solution has a pH of 7.4, whereas ALF has a pH of 4.5 and has a much higher organic content than Gamble's solution (32).…”
Section: Pulmonary Routementioning
confidence: 99%
“…The development of specialised fluids to mimic other parts of the human respiratory system is also required, as particles in the lung can also be phagocytized, exposing the PM to lower pH environments. Indeed, a growing number of studies have observed higher Pb bioaccessibility following exposure to an artificial lysosomal fluid (ALF, pH 4.5-5.0) than observed for a more neutral Gamble's-type solution (pH 7.2-7.4) (Colombo et al, 2008;Potgieter-Vermaak et al, 2012;Zereini et al, 2012). Whilst inhaled particles would have to be phagocytized before significant exposure to a more acidic environment occurs, all PM will be exposed to the neutral lung fluid.…”
Section: Introductionmentioning
confidence: 99%